Hubungan Resiliensi dengan Dukungan Keluarga Pada Remaja dengan Leukemia yang Menjalani Kemoterapi - Firdaus, Alvia Maulida; Nuryani, Reni; Wulan Lindasari, Sri (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2024)
Adolescents with leukemia who undergo chemotherapy have psychological problems caused by the side effects of treatment. Side effects that arise in adolescents with cancer include anxiety, body image disturbances, depression, decreased socialization, and even fear of death. These psychological problems can affect resilience to maintain a resilient attitude in undergoing treatment. One of the protective factors in building resilience is family support. The purpose of this study was to determine the relationship between resilience and family support. This type of research is quantitative with a correlational design. The sample used was leukemia adolescents aged 12-18 years who underwent chemotherapy using accidental sampling technique for 1 month, consisting of 37 respondents. The research instrument was the CYRM (child youth resilience measure) questionnaire which amounted to 17 questions and the family support questionnaire amounted to 12 questions. Data were analyzed with the spearman rank test. The results showed a high level of resilience and good family support. The level of strength between variables is low (0.396) with a positive direction, and significant (p value = 0.015). Conclusion: there is a strong, positive, and significant relationship between resilience and family support in leukemia adolescents who are undergoing chemotherapy.